Differences Post-extraction Collagen-density of Wistar-rat With Aerobic and Anaerobic Interval-training - Oki, Aqsa Sjuhada; Diyatri, Indeswati; Wibawa, Kadek Gede Putra (Indonesian Journal of Dental Medicine, 2019)
Background: Tooth extraction is extracting teeth from alveolar bone. In the world, tooth loss is a disease that affects the function and aesthetics oral cavity, it causes 7.5 million Disability-Adjusted Life Year (DALY). Tooth extraction rate in Indonesia is around 24% in 2013 and 19% in 2018. Sports is one of the activities that can help accelerate wound healing after tooth extraction, this study examine differences in collagen density after tooth extraction of Wistar rats given aerobic and anaerobic interval training. Objective: To prove differences in post-extraction collagen density of Wistar Rat (Rattus norvegicus) with aerobic and anaerobic interval training. Method: Wistar rats were divided into 3 groups, control group (K) rat were soaked in a bucket with tap water as high as the rat soles with a duration of 50% of maximum swimming ability (KRM), aerobic interval (P1) 3% load swim test with duration of  3 sets 50 % KRM exercise and 25% KRM rest, anaerobic interval P2 load 6% duration 80% KRM exercise and rest with 4 sets. All groups were observed on the 3rd and 7th day post extraction. Data were analyzed using Kruskal-Wallis and continued with Post-hoc test to test differences between groups. Results: There was only significant difference in collagen thickness between groups K(3) and K7, and another groups had not significant difference. Conclusion: there unsignificant differences in collagen density after tooth extraction in Wistar rats (Rattus norvegicus) with aerobic and anaerobic interval training.